THE SYSTEM OF MONITORING AND EVALUATION OF STUDENT KNOWLEDGE IN HIGHER EDUCATION INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, the full development of the individual is an important and fundamental goal and task of society. To train personnel in Uzbekistan a lot of attention is being paid. One of the main principles of the education system is to raise the level of mastery of students.Monitoring and evaluation of students' knowledge and intellectual development is important at the national level. At the same time, the process of monitoring and evaluation affects the development and upbringing of the student's personality. Assessment is the process of measuring the level of achievement of learning objectives at a certain stage of the educational process on the basis of predetermined criteria, identifying and analyzing the results. Checking and assessing the acquisition of learning materials, skills and competencies by learners is a necessary part of the learning process. It is not only about monitoring learning outcomes, but also guiding learners ’learning activities at different stages of the learning process.